Revision of Business Content on Corporate Social Responsibility: Measuring the Impact of Training on the Cognitive Effort of Second-Language University Students - Rossetti, Alessandra; Van Waes, Luuk (HERMES - Journal of Language and Communication in Business, 2022)
With more and more people interested in how sustainable and socially responsible companies are, the comprehensibility of content on corporate social responsibility (CSR) has become paramount. Producing easy-to-read business content – either by writing it from scratch or revising it – is a cognitively demanding undertaking, especially for second-language non-professional writers. Both formal training and sustained practice can help writers build expertise and, in turn, be considerate of their intended audience. In particular, research on the impact of training has usually yielded positive results when examining the texts produced following specific instruction. However, the extent to which training has a positive effect on the process of writing and revision is still under-researched, especially in second language. To address this gap, we report on an experimental study that examines the impact of reader-oriented training on the cognitive effort experienced by 47 second-language university students when revising CSR content. We adopted a pre-test post-test design, and we used keystroke logging and retrospective interviews to collect data on students’ pausing behaviour, use of online sources, and strategies to approach the revision task. Our training seemed to reduce the cognitive effort linked with lexical choices. Furthermore, it provided some students with procedural knowledge on how to approach the revision task in a more efficient way. We also observed a general tendency to rewrite (rather than revise) CSR content despite the higher cognitive effort required by rewriting. We discuss implications for training, limitations, and future research avenues.